EFFECTS OF STEROID HORMONES UPON TH1/TH2 CYTOKINE PRODUCTION BY CD45RO+ T CELLS - A. A. Gutsol; L. S. Litvinova (Медицинская иммунология, 2014)
Abstract. The aim of our study was to evaluate effects of steroid hormones upon the imbalance of Th1/Th2 cytokine production (IL-2, IFNγ, IL-4, IL-10) by CD45RO+ activated lymphocytes. In our experiments, we have shown a clear trend of multidirectional influence of steroid hormones upon secretory activity of T-lymphocytes. We have revealed that development of cellular immune responses mediated by type 1 T helper cells is regulated primarily by female sex hormones. Glucocorticoid hormones seem to exert a marked effect upon development of humoral Th2 immune response. For androgens, some controversial results have been obtained.